The management of nurses in family health strategy - Francisco Erasmo Lima de Oliveira; Suzana Carneiro de Azevedo Fernandes; Lucineire Lopes de Oliveira; Johny Carlos de Queiroz; Virgínia Rose Carneiro de Azevedo (Rev Rene)
This study aims to understand how workers in the nursing team, working in the Family Health Strategy, view the managerial role of the nurse as manager of the team. It is an exploratory research with a qualitative approach. Data were collected by means of interviews with professionals of the nursing staff of the Family Health Strategy in the city of Mossoró from October 2010 to January 2011. As a result we can see that the nurse is aware of the knowledge regarding the management of nursing. However, the nurse has not succeeded in putting into practice a participatory management, democratic, viable that will develop and promote excellence in health care according to the current public health policy. We conclude that managerial function can be regarded as an instrument of ruling and technically organize the working process with the goal of elevating the quality of nursing care and health transformation in a major locus of the construction of citizenship.